LANDASAN PEMIKIRAN PENJATUHAN PIDANA PEMECATAN TERHADAP MILITER PELAKU TINDAK PIDANA UMUM: Ahmad FirmanTarta - admin, admin; Hariz Hamdallah, Muhammad Andika (Reformasi Hukum, 2018)
The military when committing a general criminal offense can be sentenced to a crime contained in the provisions of general criminal law. The problem that arises later is that military judges in their decisions impose criminal dismissals of military members from perpetrators of general crimes. Whereas in the provisions of the Criminal Code that regulate general crimes do not recognize criminal dismissal. This study aims to determine the basic considerations used by military judges in enforcing criminal dismissals against perpetrators of general crimes. The basic considerations used by military judges in dropping criminal offenses against perpetrators of military general crimes, namely the military other than military criminal law (KUHPM) also apply general criminal law (KUHP), so that the military committing general crimes can be punished as stipulated in (KUHPM) with sentence of dismissal. In addition, there are criminal provisions for dismissal as additional crimes, military character and the verdict of capital punishment or life imprisonment